Zenker's diverticulum misinterpreted as a thyroid mass: Case report. (December 2020) - Salimi, Fatemeh; Vishani Loyala, Jerocin; Pervaiz, Arbaaz; Winter, Stuart
Abstract: We discuss an unusual presentation of Zenker's Diverticulum (ZD). A 76-year-old man presented with a left sided neck mass which was misdiagnosed as a thyroid mass due to the anatomical location and size. The ultrasound and fine needle-aspiration cytology findings were inconclusive, and a CT scan was then considered which reported a large pharyngeal pouch. Our recommendation is to consider an early CT scan in patient's where there is a clinical suspicion or risk factors for the development of pharyngeal pouch specially when the fine-needle aspiration cytology findings are inconclusive. This would reduce the risk of a delayed diagnosis which can prevent potential perforation of the pharyngeal pouch and development of mediastinitis. Highlights: Left sided neck mass misdiagnosed as thyroid mass. Zenker's Diverticulum is formed due to muscular weakness. Pharyngeal pouch symptoms mimic head and neck cancer presentation. Barium swallow is a gold standard investigation for pharyngeal pouch. Pharyngeal pouch can be treated with endoscopic or external surgical approaches.